Free Choline, but Not Phosphatidylcholine, Elevates Circulating Trimethylamine-N-oxide and This Response Is Modified by the Gut Microbiota Composition in Healthy Men - Cho, Clara (Curr Dev Nutr, 2020)
OBJECTIVES: Trimethylamine-N-oxide (TMAO), a choline-derived gut microbiota-dependent metabolite, is a newly recognized risk marker for cardiovascular disease. However, the contributions of different forms of choline and gut microbiota composition on TMAO production are largely unknown. The objectives of this study were to: 1) compare acute TMAO response to meals containing free choline (choline bitartrate) versus fat-soluble choline (phosphatidylcholine) and 2) to determine the effects of gut microbiota composition on TMAO response. METHODS: In a controlled, double-blinded, cross-over study, healthy men (n = 37) were provided meals containing (i) 600 mg choline as choline bitartrate (free choline); (ii) 600 mg choline as phosphatidylcholine; or (iii) no choline control in a random order. Blood and urine samples were collected at baseline and throughout the 6-h study period; a one-time stool sample was collected at baseline. RESULTS: Compared to no choline and phosphatidylcholine, free choline yielded 295% higher plasma TMAO (P = 0.002) and 250% higher urinary TMAO (P = 0.01), with no difference in TMAO response between phosphatidylcholine and no choline. High-TMAO producers (those with ≥40% increase in urinary TMAO response to free choline) had significantly different beta-diversity measures (unweighted UniFrac; PERMANOVA P = 0.01) compared to low-TMAO producers (those with <40% increase in TMAO response) but showed no difference in alpha-diversity. Analysis of Composition of Microbiomes (ANCOM) revealed that high-TMAO producers had more abundant lineages of Clostridium from Ruminococcaceae and Lachnospiraceae (in phylum Firmicutes) compared to low-TMAO producers (P < 0.05 with the strength of the ANCOM test W = 11 and W = 8, respectively). CONCLUSIONS: Given that the majority of choline in food is in the form of phosphatidylcholine, the absence of TMAO elevation with phosphatidylcholine counters arguments that dietary choline should be avoided for TMAO-producing characteristics. Further, development of individualized dietary recommendations based on the gut microbiota composition may be a more appropriate strategy to reduce risk of cardiovascular disease. FUNDING SOURCES: This research was supported by the Utah Agricultural Experiment Station Seed Grants Program.